PEMBUATAN KARTU TANDA PENDUDUK (KTP) DALAM PENINGKATAN PELAYANAN MASYARAKAT DI KECAMATAN MARGA KABUPATEN TABANAN, PROVINSI BALI - Artha Wibawa, I Ketut Sukantha (Universitas 17 Agustus 1945 Surabaya, 2015)
The function of the Goverment to give a help to the people to make Identity Card orFamily Card. In the absence of a formal identity document, driving licences can be usedin many countries as a method of proof of identity, although some countries do notaccept driving licences for identification, often because in those countries they don'texpire as documents and can be old and easily forged. Most countries accept passportsas a form of identification. Abstract People Identity Card or KTP is a demographicdocument that contains security systems or controlling for both the administration andinformation technology based on national demographic database. Residents are onlyallowed to have 1 (one) Identity Card that listed the Personal Identification Number(NIK). NIK is a single identity of each resident and is valid for a life. The Method thatis used in this research is descriptive in which it is conducted through qualitativeapproach. Based on the result of the research of the people in Marga toward the serviceof Government in Marga District, Tabanan Regency regarding the making of residentIdentity Card (KTP) could be categorized as good. This is caused by three aspect as theconsideration. The first aspect is cognitive, showing the fact that the Government ofMarga District in Tabanan Regency has considerably appropriate knowledge to doservice in making KTP Generally, the respondens give responses that the officer whoare responsible in this project know the mechanisms and the service in making the KTP.The second aspect is affective, showing that people feell excited with the service ofKTP making given by the Government of Marga District in Tabanan Regency. It meansthe service given by the officers of Marga District gives comport and happiness to thepeople in making the KTP. The third aspect is evaluative. Generally people judge thatthe service in making the KTP in the District of Marga in Tabanan Regency has donewell, the better service given by the Government will give the better feedback from thepeople as the Citizens.Key Word : Making Resideent Identity Card, Public Service to People